The Naming of People with Disabilities and People Experiencing Illness in the Context of Medical Students’ Linguistic Awareness - Rybicka, Julia (Representations of Disability in Cultural Spaces, 2026)
The aim of this study was to assess the linguistic knowledge of students from the Medical University of Łódź regarding terminology for people with disabilities and those with illnesses (both mental and physical). The study aimed to determine whether medical students at UMED pay attention to the negative connotations of the terms they use in their academic and professional practice and whether they are aware of inclusive language. The research was conducted using a survey in which a total of 64 students from various medical fields participated. The survey included both closed and open-ended questions, and its structure was based on recommendations from experts at the Polish Language Council, Judy Cohen’s guidelines, and suggestions from linguists at the University of Warsaw. Quantitative and qualitative analyses showed that, although students demonstrate linguistic sensitivity, their knowledge of inclusive communication is incomplete. The study revealed the need to introduce courses in inclusive language to enable these future professionals to approach patients with greater empathy and respect, avoiding stigmatizing language that could deepen the sense of exclusion among people dealing with various limitations.